Distributed consensus of heterogeneous multi-agent systems subject to switching topologies and delays - Meng, Min (2021)
In this paper, the problem of distributed output consensus is investigated for heterogeneous multi-agent systems subject to a class of uncertainties in communication channels. The studied uncertainties, leading to a time-varying communication topology modeled as a Markovian switching communication topology and delayed transit information, may happen discontinuously and affect the consensus behavior of multi-agent systems. To mitigate the effects of such uncertainties on output consensus, a novel switching distributed control protocol is proposed, aiming to guarantee output consensus of the studied networks in the mean square sense. Moreover, an algorithm is given to select the required controller gains based on the solutions to a Lyapunov inequality and a group of regulator equations. Along this framework, a simulation example on the IEEE 24 Bus System is presented to demonstrate the effectiveness of the algorithm and the theoretical results.